2020
DOI: 10.20473/jbe.v8i12020.89-96
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Immunization Status and Mother’s Height, and Stunting in Children 2–5 Years in Indonesia

Abstract: Background: Stunting is a condition where the growth and development of a child fails during the first 1,000 days of life. The number of stunted children in Indonesia has increased from 35.60% in 2010 to 37.20% in 2013. Purpose: The aim of this study is to analyse the relationship between immunisation status and stunting in children 2–5 years. Methods: This is a secondary data analysis with cross-sectional study design. The data used for this study were obtained from Indonesia Family Live Survey wave 5. IFLS 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
11
0
9
Order By: Relevance
“…Repeated infections can interfere with a child's growth and development if it happens over a long period of time 30 . One previous study reported a significant relationship between immunisations and stunting 31 . Although BCG vaccine does not influence stunting in children its timing is crucial 32 ; BCG is related to a lower risk of stunting if carried out in early life.…”
Section: Discussionmentioning
confidence: 93%
“…Repeated infections can interfere with a child's growth and development if it happens over a long period of time 30 . One previous study reported a significant relationship between immunisations and stunting 31 . Although BCG vaccine does not influence stunting in children its timing is crucial 32 ; BCG is related to a lower risk of stunting if carried out in early life.…”
Section: Discussionmentioning
confidence: 93%
“…Hasil: Penelitian ini menunjukkan bahwa terdapat hubungan antara status vaksinasi (p = 0,01; OR =1,78 ; 95% CI = 1.26 <OR< 2.52), tinggi badan ibu (p = 0,00; OR = 1,41; 95% CI = 1.00 <OR< 1.98) memiliki hubungan dengan kejadian stunting pada anak usia 2-5 tahun. Kesimpulan: Status vaksinasi dan tinggi ibu memiliki hubungan dengan kejadian stunting pada anak usia 2-5 tahun (Fajariyah, & Hidajah, 2020).…”
Section: Hubungan Status Imunisasi Terhadap Kejadian Stuntingunclassified
“…Previous studies reported that cases of stunted toddler and wasting were found to be more in children with incomplete immunization status 12,13 i.e., BCG; measles; polio 3; and Diphtheria, Tetanus toxoids, and Pertussis, i.e., DTP3. Apart from having an impact on the nutritional status of children under five, immunization is needed because it is an effort to reduce child morbidity and mortality 14 . Table 4 shows the cross-tabulation between stunted toddler prevalence and coverage of households accessing healthy latrines in East Java Province.…”
Section: Table 3 Cross-tabulation Between Stunted Toddler Prevalencementioning
confidence: 99%